If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying q(5 + -1q) = 0 (5 * q + -1q * q) = 0 (5q + -1q2) = 0 Solving 5q + -1q2 = 0 Solving for variable 'q'. Factor out the Greatest Common Factor (GCF), 'q'. q(5 + -1q) = 0Subproblem 1
Set the factor 'q' equal to zero and attempt to solve: Simplifying q = 0 Solving q = 0 Move all terms containing q to the left, all other terms to the right. Simplifying q = 0Subproblem 2
Set the factor '(5 + -1q)' equal to zero and attempt to solve: Simplifying 5 + -1q = 0 Solving 5 + -1q = 0 Move all terms containing q to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1q = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1q = 0 + -5 -1q = 0 + -5 Combine like terms: 0 + -5 = -5 -1q = -5 Divide each side by '-1'. q = 5 Simplifying q = 5Solution
q = {0, 5}
| 3y=-28-x | | 2(1+x)-1=3(2x+1)+2 | | z-48=-32 | | (5-q)-5q= | | 8x-1/5-1=(50-2x/9)+(3x+3/4) | | 16x+7x+15=0 | | 5-q= | | 10n=4 | | 5x-4=14x-13 | | 3x+26=10x-41 | | 20*(4x+1)-24(3x+1)=15*60-60*(25-x) | | 15x-176=6x-14 | | 24*(3x-1)-20*(5x+1)=120*(x+1)-3*120 | | 6y+(8)(7)-4=42 | | 11x+2=2x+128 | | 155-5x=40x+15x | | 7-10x=55-24x | | x^2+16x+9=18 | | 145-8x=8x+15 | | 182-6x=5x+24 | | 2x+96=9x-9 | | 81-5x=22x+21 | | 8-8x=68-36x | | 4x^2-12x-91=0 | | h=20+50t-16t^2 | | t+5=3t+5 | | 38-4x=5x+23 | | 11-8x=131-36x | | 124-7x=11x+24 | | 7-9x=85-23x | | 10x-8=8x+12 | | 10+12=54+x |